Ways to Reduce Ore Losses and Dilution in Iron Ore Underground Mining in Kryvbass - Azaryan, A.A.; Batareyev, O.S.; Karamanits, F.I.; Kolosov, V.O.; Morkun, V.S. (Science and Innovation, 2024)
Introduction. Ukraine’s economic potential greatly depends on efficient operation of the national mining and metallurgical complex that provides 30% of GDP. One of the essential structural branches of the mining and metallurgical complex is iron ore mining industry. The quality of iron ore materials is the primary indicator ensuring their competitiveness in domestic and foreign markets. The quality of iron ore products is formed in the course of ore mining and processing into marketable products. Problem statement. Worsening ore quality and losses is a serious problem in iron ore underground mining. It is caused by incomplete extraction of iron ore reserves (72-75% of the producing reserves) while breaking and drawing as well as by ore dilution with waste rocks, which causes an iron content reduction by 1.5-12% as compared with the initial iron content in the massif. Purpose. The research aims at analyzing reasons for high ore losses and dilution in underground ore mining at Kryvyi Rih iron ore basin and at searching ways to reduce them. Materials and methods. Analysis of known methods for solving the given problem has revealed that it is quite efficient to create an organizational and technical system that enables to forecast, to detect, and to promptly solve the reasons causing excessive ore losses and dilution. Results. To efficiently control qualitative and quantitative parameters of ore at all stages of mining, transportation, and processing, an automated working place, Quality AWP, which provides data collection and representation at all stages of mining production at the central server is suggested to apply for continuous monitoring and analysis of ore quality characteristics. Conclusions. Introduction of the complex of technical means and Quality AWP automated system enables tracking the ore qualitative characteristics on a continuous basis and reducing ore losses by 3% and dilution by 2%.